Prevalence of Infection-Competent Serogroup 6 Legionella pneumophila within Premise Plumbing in Southeast Michigan - Brenda G. Byrne (American Society for Microbiology, 2018)
ABSTRACT Coinciding with major changes to its municipal water system, Flint, MI, endured Legionnaires’ disease outbreaks in 2014 and 2015. By sampling premise plumbing in Flint in the fall of 2016, we found that 12% of homes harbored legionellae, a frequency similar to that in residences in neighboring areas. To evaluate the genetic diversity of Legionella pneumophila in Southeast Michigan, we determined the sequence type (ST) and serogroup (SG) of the 18 residential isolates from Flint and Detroit, MI, and the 33 clinical isolates submitted by hospitals in three area counties in 2013 to 2016. Common to one environmental and four clinical samples were strains of L. pneumophila SG1 and ST1, the most prevalent ST worldwide. Among the Flint premise plumbing isolates, 14 of 16 strains were of ST367 and ST461, two closely related SG6 strain types isolated previously from patients and corresponding environmental samples. Each of the representative SG1 clinical strains and SG6 environmental isolates from Southeast Michigan infected and survived within macrophage cultures at least as well as a virulent laboratory strain, as judged by microscopy and by enumerating CFU. Likewise, 72 h after infection, the yield of viable-cell counts increased >100-fold for each of the representative SG1 clinical isolates, Flint premise plumbing SG6 ST367 and -461 isolates, and two Detroit residential isolates. We verified by immunostaining that SG1-specific antibody does not cross-react with the SG6 L. pneumophila environmental strains. Because the widely used urinary antigen diagnostic test does not readily detect non-SG1 L. pneumophila, Legionnaires’ disease caused by SG6 L. pneumophila is likely underreported worldwide. IMPORTANCE L. pneumophila is the leading cause of disease outbreaks associated with drinking water in the United States. Compared to what is known of the established risks of colonization within hospitals and hotels, relatively little is known about residential exposure to L. pneumophila. One year after two outbreaks of Legionnaires’ disease in Genesee County, MI, that coincided with damage to the Flint municipal water system, our multidisciplinary team launched an environmental surveillance and laboratory research campaign aimed at informing risk management strategies to provide safe public water supplies. The most prevalent L. pneumophila strains isolated from residential plumbing were closely related strains of SG6. In laboratory tests of virulence, the SG6 environmental isolates resembled SG1 clinical strains, yet they are not readily detected by the common diagnostic urinary antigen test, which is specific for SG1. Therefore, our study complements the existing epidemiological literature indicating that Legionnaires’ disease due to non-SG1 strains is underreported around the globe.